2015
DOI: 10.1155/2015/318901
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Left Atrial Appendage Exclusion Does Not Impair Left Atrial Contraction Function: A Pilot Study

Abstract: Background. In order to reduce stroke risk, left atrial appendage amputation (LAAA) is widely adopted in recent years. The effect of LAAA on left atrial (LA) function remains unknown. The objective of present study was to assess the effect of LAAA on LA function. Methods. Sixteen patients with paroxysmal AF underwent thoracoscopic, surgical PVI with LAAA (LAAA group), and were retrospectively matched with 16 patients who underwent the same procedure without LAA amputation (non-LAAA group). To objectify LA func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 26 publications
3
16
1
1
Order By: Relevance
“…Several studies have reported that LAA contractile function contributes greatly to LA transport function. Benussi et al 26) studied the effects of LAA amputation on left atrial function in the setting of minimally invasive surgical pulmonary vein isolation and found that the LA reservoir and conduit function are impaired after procedure. This might contribute to the decreased LA compliance resulting from the postoperative adhesions of the pericardium and/or atrial surgical scarring.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that LAA contractile function contributes greatly to LA transport function. Benussi et al 26) studied the effects of LAA amputation on left atrial function in the setting of minimally invasive surgical pulmonary vein isolation and found that the LA reservoir and conduit function are impaired after procedure. This might contribute to the decreased LA compliance resulting from the postoperative adhesions of the pericardium and/or atrial surgical scarring.…”
Section: Discussionmentioning
confidence: 99%
“…Thrombus is formed in the left atrial appendage (LAA) in up to 90% of cases, which may lead to embolism (1,4). To prevent this, the LAA may be closed either surgically or interventionally (1,5).…”
Section: Introductionmentioning
confidence: 99%
“…Various surgical techniques are applicable from an external, epicardial approach as well as from an internal, endocardial approach. Externally, the spectrum includes simple ligature or surgical suturing at the base, surgical stapling [14][15][16], and clipping with an AtriClip commercial device (AtriCure, West Chester, OH) [5,[17][18][19][20][21], which is Conformit e Europ eene marked and U.S. Food and Drug Administration approved. External, epicardial techniques are used in combination with other cardiac procedures or as stand-alone procedures, which can also be performed in a minimally invasive manner [22][23][24].…”
mentioning
confidence: 99%